Replication and Injury Associated With SARS-CoV-2 in Cultured Hepatocytes - Suman Pradhan; Susan D. Rouster; Jason T. Blackard; Gary E. Dean; Kenneth E. Sherman (Case Western Reserve University, 2024)
Background: Liver dysfunction is one of the hallmarks of SARS-CoV-2 infection. The mechanism(s) of hepatic injury in SARS-CoV-2 infection remains controversial with some reporting viral replication and cellular injury and others suggesting lack of replication and injury due to non-cytopathogenic etiologies. To investigate this further, we evaluated SARS-CoV-2 replication in immortalized hepatic cell lines and primary hepatocytes, examined whether cell injury was associated with apoptotic pathways, and also determined the effect of the antiviral remdesivir on these processes. Methods: Immortalized hepatocyte cell lines (HepG2 and Huh7.5), as well as primary human hepatocytes, were exposed to SARS-CoV-2 at a multiplicity of infection of 0.1 PFU/mL. Viral replication was evaluated by plaque assays, immunohistochemical staining for the viral spike protein, and caspase-3 expression evaluated with and without exposure to remdesivir.  Results: All hepatocyte cell lines and primary hepatocytes supported active replication of SARS-CoV-2. Significant cytopathic effect was observed by light microscopy, and caspase-3 staining supported activation of apoptotic pathways. Remdesivir abrogated infection in a dose-dependent fashion and was not independently associated with hepatocyte injury. Conclusion: Hepatocytes appear to be highly permissive of SARS-CoV-2 replication which leads to rapid cell death associated with activation of apoptotic pathways. Viral replication and hepatocytes injury are abrogated with remdesivir. We conclude that active viral replication is most likely a key contributor to liver enzyme abnormalities observed in the setting of acute SARS-CoV-2 infection.